2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5333648
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pulsatile wall shear stress in compliant arteries: Numerical model, validation and experimental data

Abstract: There is evidence that wall shear stress (WSS) is associated with vascular disease. In particular, it is widely accepted that vascular segments with low or oscillatory values of WSS are more probable to develop vascular disease. It is then necessary to establish a realistic model of the blood flow in blood vessels in order to determine precisely WSS. We proposed a numerical 1D model which takes into account the pulsatile nature of blood flow, the elasticity of the vessel, and its geometry. The model allows the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
1
Order By: Relevance
“…Aricò et al [60] and Silva et al [61] implemented meshless models and reported significant reductions in computational effort. ROM was also suggested as an efficient technique to estimate haemodynamics accurately and reduce reporting time [48,53,117,118]. Liu et al [93] proposed a new optimisation method (Multi-Resolution Direct Search) designed to reduce the high computational effort inherent to inverse methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aricò et al [60] and Silva et al [61] implemented meshless models and reported significant reductions in computational effort. ROM was also suggested as an efficient technique to estimate haemodynamics accurately and reduce reporting time [48,53,117,118]. Liu et al [93] proposed a new optimisation method (Multi-Resolution Direct Search) designed to reduce the high computational effort inherent to inverse methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…The numerical model presented small errors in pressure and flow measurements, thus proving to be able to accurately capture the main haemodynamic features. Salvucci et al [117] estimated planar WSS using 1D models of the thoracic aorta. The group of Bollache et al [49] developed 1D models based on patient-specific data obtained via CT and MRI scans.…”
Section: Novel Numerical Techniquesmentioning
confidence: 99%
“…Propuestas de control no lineal. Modelo matemático de funcionamiento de corto circuito hidráulico anómalo [5]. Equipamiento para personas con capacidades diferentes Diseño y desarrollo de sistema de bipedestación con funciones automáticas controladas por DSP-PIC.…”
Section: Tabla 4 Líneas Prioritarias Y Proyectos Asociadosunclassified